Method for preparing positive electrode active material for lithium secondary battery, and lithium secondary battery

By eliminating the transition metal precursor in the preparation of the positive electrode active substance of lithium secondary battery, wet nano-grinding and mechanical drying technology are used to prepare lithium-containing compounds in a single crystal shape, solving the problems of environmental pollution and low density, and realizing lithium High performance and low cost of secondary batteries.

CN119430312APending Publication Date: 2025-02-14权镐真
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311441267.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-03
Filing Date
2023-11-01
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

The existing method of preparing positive electrode active substances for lithium secondary batteries uses transition metal precursors, which leads to environmental pollution, especially water quality pollution, and the prepared polycrystalline particle density is low, which limits the performance of lithium secondary batteries.

Method used

By eliminating the transition metal precursor, mechanical drying is performed using wet nano-grinding and planetary dispersion mixer to prepare lithium-containing compounds in a single crystal shape. This method can evenly distribute lithium in the single crystal shape, improving the stability of the crystal structure.

Benefits of technology

The high-efficiency preparation of lithium-containing compounds in single crystal shape is achieved, and the stability, thermal stability and high temperature life characteristics of the high-voltage charging structure of lithium secondary batteries are improved, ensuring the high capacity and low price characteristics of lithium secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430312A_ABST
    Figure CN119430312A_ABST
Patent Text Reader

Abstract

The present invention relates to a positive electrode active material for a lithium secondary battery, a method for preparing the same, and a lithium secondary battery comprising the same, the method comprising the steps of: (a) respectively preparing a first raw material containing a lithium-containing raw material and a second raw material containing at least one material selected from the group consisting of a nickel-containing raw material, a cobalt-containing raw material, a manganese-containing raw material, an iron-containing raw material, and an aluminum-containing raw material; (b) preparing a nanoslurry by wet nanogrinding a solution in which the first raw material and the second raw material are dissolved and dispersed; (c) preparing nanoparticles by mechanically drying the nanoslurry after the nanoslurry is introduced into a planetary dispersion mixer; and (d) firing the mechanically dried nanoparticles to produce a lithium-containing compound having a single crystal shape.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a method for preparing a positive electrode active material for a high-performance lithium secondary battery by a novel process excluding the use of a transition metal precursor, and a lithium secondary battery using the same. Background Art

[0002] The energy device that has attracted the most attention recently in the fields of IT, electric vehicles (EV), and energy storage devices (ESS) is the lithium secondary battery. Since Sony first commercialized it globally in 1990, lithium secondary batteries have developed significantly in the past 30 years. Initially, the application field was limited to mobile fields such as mobile phones and laptops, but recently, its application field has expanded to electric vehicles and large-scale energy storage devices, and it is continuing to develop. In particular, with the emergence of environmental protection and efficiency issues, the electric vehicle and energy storage device fields have expanded to new business fields, and the application field of lithium secondary batteries has expanded rapidly. Initially, lithium secondary batteries used in the IT field can be applied as long as they simply achieve the life and capacity targets. As the application field of lithium secondary batteries expands to the electric vehicle and energy storage device fields, the demand for improved performance of lithium secondary batteries continues to increase. In this field, it is necessary to achieve capacity, life targets, safety, reliability, and especially, to achieve extremely low prices.

[0003] Therefore, it is necessary to develop positive electrode active materials for lithium secondary batteries that can be applied to various application fields such as the IT field, electric vehicles, and energy storage devices.

[0004] Prior art literature

[0005] Patent Literature

[0006] Korean Patent Gazette No. 10-1871919 (June 21, 2018) Summary of the invention

[0007] The object of the present invention is to provide a method for preparing a positive electrode active material for a lithium secondary battery, etc., which eliminates the use of a transition metal precursor commonly used in the existing method for preparing a positive electrode active material for a lithium secondary battery and adopts a new process. The method for preparing a positive electrode active material for a lithium secondary battery comprises: step (a), respectively preparing a first raw material containing a lithium raw material and a second raw material containing at least one selected from a group consisting of a nickel-containing raw material, a cobalt-containing raw material, a manganese-containing raw material, an iron-containing raw material and an aluminum-containing raw material; step (b), preparing a nano-slurry by wet nano-grinding a solution in which the first raw material and the second raw material are dissolved and dispersed; step (c), after the nano-slurry is put into a planetary dispersive mixer, mechanically drying it to prepare nanoparticles; and step (d), calcining the mechanically dried nanoparticles to prepare a lithium-containing compound in a single crystal shape.

[0008] However, the technical problems to be solved by the present invention are not limited to the problems mentioned above, and ordinary technicians in the technical field to which the present invention belongs can clearly understand other problems not mentioned from the following description.

[0009] The present invention provides a method for preparing a positive electrode active material for a lithium secondary battery, which comprises: step (a), respectively preparing a first raw material containing a lithium-containing raw material and a second raw material containing at least one selected from a group consisting of a nickel-containing raw material, a cobalt-containing raw material, a manganese-containing raw material, an iron-containing raw material and an aluminum-containing raw material; step (b), preparing a nano-slurry by wet nano-grinding a solution in which the first raw material and the second raw material are dissolved and dispersed; step (c), putting the nano-slurry into a planetary dispersive mixer and then mechanically drying it to prepare nano-particles; and step (d), calcining the mechanically dried nano-particles to prepare a lithium-containing compound in a single crystal shape.

[0010] In the above step (a), the second raw material may be in the form of an oxide or a hydroxide.

[0011] In the above step (a), i) when the second raw material contains both nickel-containing raw material and manganese-containing raw material, it may also contain at least one doped metal oxide selected from the group consisting of aluminum oxide (Al2O3), titanium dioxide (TiO2), zirconium dioxide (ZrO2), molybdenum hexaoxide (MoO6) and tantalum pentoxide (Ta2O5); ii) when the second raw material contains iron-containing raw material, it also contains PO4-containing raw material.

[0012] The present invention may further include step ii), after dry mixing the second raw material containing the above-mentioned iron-containing raw material and the PO4-containing raw material, pre-calcining is performed at a temperature of 150° C. to 200° C. for 5 to 20 hours.

[0013] In the above step (b), the volume ratio of the above raw materials to the solvent in the solution can be 1:1 to 1:5.

[0014] In the above step (b), the wet nano-milling may be performed at a speed of 1000 rpm to 5000 rpm for 1 hour to 5 hours.

[0015] In the above step (b), in the particle distribution of the nano-slurry, 0.1 μm≤D50≤0.5 μm, Dmax<1 μm.

[0016] In the above step (c), a jacket having a circulation flow path for circulating a heating fluid may be further provided on the outer surface of the planetary disperser, and the heating fluid is maintained at a temperature of 50°C to 200°C.

[0017] In the above step (c), the mechanical drying may be performed under vacuum conditions.

[0018] In the above step (d), the sintering may be performed at a temperature of 600° C. to 1000° C. for 5 to 20 hours.

[0019] After the above step (d), the following step may be further included: forming a surface treatment layer on the above single crystal lithium-containing compound, wherein the surface treatment layer contains Al(OH) 3 , a boron-containing compound and a silicon-containing compound.

[0020] In one embodiment of the present invention, a positive electrode active material for a lithium secondary battery prepared by the above method is provided.

[0021] In another embodiment of the present invention, a lithium secondary battery including the positive electrode active material is provided.

[0022] The method for preparing a positive electrode active material for a lithium secondary battery of the present invention has the following advantages: eliminating the use of a transition metal precursor, performing wet nano-grinding on a solution for dissolving and dispersing each raw material (raw material in oxide form or hydroxide form), and then putting it into a planetary disperser and mechanically drying it, a lithium-containing compound in a single crystal shape can be easily prepared with high efficiency. Depending on the situation, raw materials obtained from lithium ion waste batteries by a wet process are used as each raw material, thereby solving environmental problems that occur when preparing transition metal precursors, especially water pollution problems.

[0023] The positive electrode active material for lithium secondary batteries prepared according to the present invention has the following advantages: as lithium is evenly distributed in a single crystal shape, the crystalline structure can be stabilized compared to a polycrystalline shape. As a result, under high-voltage charging conditions, the structural stability is excellent, thereby ensuring the high-capacity characteristics of the lithium secondary battery, and under high-temperature conditions, it has excellent characteristics, thereby ensuring the high-temperature life, recovery and maintenance characteristics of the lithium secondary battery. In particular, compared to a polycrystalline shape, the thermal stability is excellent, thereby improving the stability of the lithium secondary battery.

[0024] That is, the lithium secondary battery using the high-performance and low-cost positive electrode active material prepared according to the present invention has the advantages of excellent performance such as discharge capacity and efficiency, C-rate, and normal temperature and high temperature life characteristics. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1a Schematic diagram of a stirrer for dissolving and dispersing in Example 1, Figure 1b A photograph showing the wet nano-milling apparatus used for wet nano-milling in Example 1, Figure 1c This is a graph showing the particle distribution of the nano slurry of Example 1. Figure 1d This is a photograph showing the planetary disperser used in Example 1.

[0026] Figure 2a and Figure 2b Graphs comparing the C-rate and 0.1C capacity of the button batteries of Example 2 and Comparative Example 1, respectively.

[0027] Figure 3 This is a chart comparing the 0.1C capacities of the button batteries of Example 3 and Comparative Example 2.

[0028] Figure 4a The SEM images of the lithium-containing compounds of Comparative Example 4 and Comparative Example 3 are shown in FIG. Figure 4b and Figure 4c The following are graphs comparing the 0.1C capacity and room temperature life of the button batteries of Example 4 and Comparative Example 3, respectively.

[0029] Figure 5a is a graph showing the XRD pattern of the lithium-containing compound of Example 5, Figure 5b The SEM images of the lithium-containing compounds of Comparative Example 5 and Comparative Example 4 are shown in FIG. Figure 5c This is a chart comparing the 0.1C capacities of the button batteries of Example 5 and Comparative Example 3.

[0030] Figure 6a A graph showing the 0.1C capacity of the button cell of Example 6, Figure 6b A graph showing the high temperature life of the button battery of Example 6.

[0031] Figure 7a is a SEM photograph of the lithium-containing compound of Comparative Example 7, Figure 7b This is a graph comparing the XRD patterns of the lithium-containing compound of Example 7 at each sintering temperature. Figure 7c to Figure 7e The following are graphs comparing the 0.1C capacity, high temperature life, and C-rate of the button batteries of Example 7 and Comparative Example 5, respectively.

[0032] Figure 8 This is a graph showing the 0.1C capacity of the button cells of Comparative Example 8. DETAILED DESCRIPTION

[0033] As shown in the preparation method of the positive electrode active material for the existing lithium secondary battery, when the lithium-containing raw material and the transition metal precursor (optionally, doped with metal oxide) are dry-mixed and then sintered, multiple raw materials cannot be evenly distributed. Not only that, it is inevitable to prepare polycrystalline particles with low density. Therefore, the performance of the lithium secondary battery to which it is applied is limited.

[0034] In the process of conducting research on eliminating the use of transition metal precursors commonly used in the preparation method of existing positive electrode active materials for lithium secondary batteries, the inventors conducted wet nano-grinding on the solution of dissolved and dispersed raw materials (oxide form or hydroxide form raw materials), put it into a planetary disperser and mechanically dried it, confirmed that single crystal lithium-containing compounds can be easily prepared with high efficiency, and completed the present invention.

[0035] Hereinafter, the present invention will be described in detail.

[0036] Method for preparing positive electrode active material for lithium secondary battery

[0037] The present invention provides a method for preparing a positive electrode active material for a lithium secondary battery, which comprises: step (a), respectively preparing a first raw material containing a lithium-containing raw material and a second raw material containing at least one selected from a group consisting of a nickel-containing raw material, a cobalt-containing raw material, a manganese-containing raw material, an iron-containing raw material and an aluminum-containing raw material; step (b), preparing a nano-slurry by wet nano-grinding a solution in which the first raw material and the second raw material are dissolved and dispersed; step (c), putting the nano-slurry into a planetary disperser and then mechanically drying it to prepare nano-particles; and step (d), calcining the mechanically dried nano-particles to prepare a lithium-containing compound in a single crystal shape.

[0038] First, the positive electrode active material for lithium secondary battery of the present invention includes step (a), respectively preparing a first raw material containing a lithium raw material and a second raw material containing at least one selected from the group consisting of a nickel-containing raw material, a cobalt-containing raw material, a manganese-containing raw material, an iron-containing raw material and an aluminum-containing raw material.

[0039] The first raw material includes a lithium-containing raw material. For example, Li2CO3, LiOH, etc. can be used as the lithium-containing raw material.

[0040] On the other hand, the second raw material includes at least one selected from the group consisting of a nickel-containing raw material, a cobalt-containing raw material, a manganese-containing raw material, an iron-containing raw material and an aluminum-containing raw material, and can be in the form of an oxide or a hydroxide. For example, NiO, Ni(OH)2, etc. can be used as a nickel-containing raw material, Co3O4, Co(OH)2, etc. can be used as a cobalt-containing raw material, Mn3O4, Mn(OH)2, etc. can be used as a manganese-containing raw material, Fe2O3, etc. can be used as an iron-containing raw material, and Al2O3, etc. can be used as an aluminum-containing raw material. These can be commercial products or raw materials obtained from lithium-ion waste batteries by a wet process. In the case of raw materials obtained from lithium-ion waste batteries by a wet process, environmental problems occurring when preparing transition metal precursors, especially water pollution problems, can be solved. Furthermore, the second raw material can be added with a variety of known doped metal oxides such as Al2O3, TiO2, ZrO2, MoO6 and Ta2O5, and the total doping amount can be 1000ppm to 5000ppm.

[0041] Furthermore, the average particle size of the second raw material can be 100nm to 10μm, preferably, 100nm to 5μm, but it is not limited thereto. On the other hand, when the average particle size of the second raw material is too small such as hundreds of nm, when dry mixing and sintering are performed, the final lithium-containing compound is also hundreds of nm in size (for example, D50=100~500nm), so that when preparing the plate, there is a limitation of low compaction density. However, even if the average particle size of the second raw material is hundreds of nm in size, when it is put into a wet nano-grinder and a planetary disperser and then mechanically dried and sintered, the final average particle size of the lithium-containing compound can be micron-sized such as 1~10μm (preferably 1~5μm), so that when preparing the plate, a high compaction density plate can be prepared, so a high-capacity lithium secondary battery can be developed.

[0042] In particular, i) when the second raw material contains both a nickel-containing raw material and a manganese-containing raw material, it may also include at least one doped metal oxide selected from the group consisting of Al2O3, TiO2, ZrO2, MoO6 and Ta2O5, and the doping amount of each may be at the level of 500ppm to 5000ppm.

[0043] Furthermore, ii) when the second raw material contains an iron-containing raw material, it may also contain a PO4-containing raw material. For example, (NH4)3HPO4 or the like may be used as the PO4-containing raw material. Depending on the circumstances, a manganese-containing raw material or a carbon source for improving conductivity may also be added. For example, a polysaccharide such as glucose or sucrose may be used as the carbon source, and the amount added may be 1wt% to 8wt% of the total weight of the lithium-containing compound described later.

[0044] The present invention may further include the following step: after dry mixing the above-mentioned iron-containing raw material, the above-mentioned PO4-containing raw material and the second raw material optionally containing the above-mentioned manganese-containing raw material or the above-mentioned carbon source for improving conductivity, pre-sintering is performed at a temperature of 150°C to 200°C for 5 hours to 20 hours. Preferably, the pre-sintering is performed at a temperature of 160°C to 180°C for 15 hours to 18 hours, thereby each raw material can be made into a single-phase single crystal FePO4 or Mn 0.5 Fe 0.5 PO4. In this case, as the prepared FePO4 or Mn 0.5 Fe 0.5 The average particle size of PO4 is 1 to 10 μm (preferably 1 to 5 μm) or other micron-sized size, and has the characteristics of high density. When preparing the plate, a high compaction density plate can be prepared, so it can be developed into a high-capacity lithium secondary battery. On the other hand, the FP precursor used in the past was prepared by coprecipitation, and its size was hundreds of nm, and the final lithium-containing compound was also hundreds of nm in size (for example, D50 = 100 to 500 nm). Therefore, when preparing the plate, it is difficult to achieve a high-capacity lithium secondary battery due to the low compaction density.

[0045] Next, the method for preparing a positive electrode active material for a lithium secondary battery of the present invention includes the step (b) of preparing a nano slurry by wet nano-milling a solution in which the first raw material and the second raw material are dissolved and dispersed.

[0046] The first raw material and the second raw material are dissolved and dispersed to prepare a solution, in which case a stirrer may be used. The volume ratio of the multiple raw materials to the solvent in the solution may be 1:1 to 1:5, preferably 1:2 to 1:4, but is not limited thereto.

[0047] The wet nano-grinding can be performed at a speed of 1000 rpm to 5000 rpm for 1 hour to 5 hours, preferably, at a speed of 2000 rpm to 5000 rpm for 2 hours to 5 hours, but is not limited thereto. In this case, a wet nano-eye mask device can be used. In the particle distribution of the nano-slurry, it can be 0.1 μm ≤ D50 ≤ 0.5 μm (preferably, 0.1 μm ≤ D50 ≤ 0.2 μm), Dmax < 1 μm.

[0048] Next, the method for preparing a positive electrode active material for a lithium secondary battery of the present invention includes the step (c) of adding the nano slurry to a planetary dispersive mixer and then mechanically drying the slurry to prepare nano particles.

[0049] A jacket having a circulation flow path for circulating a heating fluid is also provided on the outer surface of the planetary disperser, and the heating fluid can maintain a temperature of 50°C to 200°C (preferably, a temperature of 80°C to 150°C). In addition, the mechanical drying can be performed under vacuum conditions by blowing in air or dry nitrogen to uniformly evaporate the solution. Thus, high-density single-crystal nanoparticles in which lithium is uniformly distributed can be produced.

[0050] When spray drying or the like is used instead of such mechanical drying, it is inevitable that particles having a low-density polycrystalline shape (a spherical shape with a hollow interior) are produced, in which primary particles and secondary particles are agglomerated with each other.

[0051] Next, the method for preparing a positive electrode active material for a lithium secondary battery of the present invention includes a step (d) of preparing a polycrystalline lithium-containing compound by firing the mechanically dried nanoparticles.

[0052] The calcination is performed to grow the mechanically dried nanoparticles to prepare a lithium-containing compound in a single crystal form. The calcination may be performed at a temperature of 600° C. to 1000° C. for 5 to 20 hours.

[0053] The above-mentioned lithium-containing compounds can be lithium nickel cobalt manganese compounds, lithium nickel cobalt manganese aluminum compounds, lithium nickel iron aluminum compounds, lithium nickel manganese compounds, lithium iron PO4 compounds or lithium manganese iron-PO4 compounds. Depending on the situation, various known doped metal oxides such as Al2O3, TiO2, ZrO2, MoO6 and Ta2O5 can also be added.

[0054] When the lithium-containing compound is a lithium nickel cobalt manganese compound, a lithium nickel cobalt manganese aluminum compound, a lithium nickel iron aluminum compound or a lithium nickel manganese compound, the calcination may be performed at a temperature of 600° C. to 1000° C. for 5 to 20 hours. On the other hand, when the lithium-containing compound is a lithium iron PO4 compound or a lithium manganese iron PO4 compound, the calcination may be performed at a temperature of 600° C. to 800° C. for 5 to 20 hours.

[0055] In this case, the present invention is characterized in that the lithium-containing compound evenly distributes lithium in the single crystal shape. Moreover, the single crystal shape can exist in a state where the particles are individually separated, and the average particle size can be 1μm to 5um. Moreover, the single crystal shape can be made into a layered structure without impurities. On the contrary, in the past, the positive electrode active material for lithium secondary batteries prepared using transition metal precursors was a polycrystalline shape (average particle size was 10μm to 50μm) formed by mutual condensation of primary particles and secondary particles.

[0056] Optionally, after the above step (d), a step of forming a surface treatment layer comprising Al(OH)3, a boron-containing compound and a silicon-containing compound on the above single crystal-shaped lithium-containing compound may be performed. In this case, relative to 100 parts by weight of the above Al(OH)3, 1 to 100 parts by weight of the boron-containing compound and 1 to 100 parts by weight of the silicon-containing compound may be included, and 1 to 10 parts by weight of the boron-containing compound and 1 to 10 parts by weight of the silicon-containing compound are better in terms of performance improvement, but are not limited thereto.

[0057] For the formation of the surface treatment layer, the lithium-containing compound in a single crystal form may be added to the surface treatment solution containing Al(OH)3, the boron-containing compound and the silicon-containing compound. For example, based on 1 kg of the lithium-containing compound in a single crystal form, the surface treatment solution may be 300 g to 500 g. With the surface treatment solution containing 20 g of Al(OH)3, 1 g of B2O3 and 1 g of SiO x , which can further improve performance.

[0058] Next, after mixing and drying for 1 to 10 hours at a temperature of 50° C. to 150° C., heat treatment may be performed for 1 to 10 hours at a temperature of 200° C. to 400° C. In this case, when the heat treatment temperature is greater than 400° C., Al(OH) 3 and the boron-containing compound become crystalline substances, so there is a limitation that the original effect of the surface treatment cannot be normally exerted.

[0059] Positive electrode active material for lithium secondary battery

[0060] The present invention provides a positive electrode active material for a lithium secondary battery prepared by the method.

[0061] The positive electrode active material for lithium secondary batteries of the present invention is prepared by the above method, characterized in that it includes: step (a), respectively preparing a first raw material containing a lithium raw material and a second raw material containing at least one selected from the group consisting of a nickel-containing raw material, a cobalt-containing raw material, a manganese-containing raw material, an iron-containing raw material and an aluminum-containing raw material; step (b), preparing a nano slurry by wet nano grinding of a solution in which the first raw material and the second raw material are dissolved and dispersed; step (c), after the nano slurry is put into a planetary disperser, it is mechanically dried to prepare nano particles; and step (d), calcining the mechanically dried nano particles to prepare a lithium-containing compound in a single crystal shape. "Steps (a) to (d)" have been described, so the repeated description thereof will be omitted.

[0062] In the past, the positive electrode active material for lithium secondary batteries prepared using transition metal precursors was a large particle (average particle size of 10 μm to 50 μm) in a polycrystalline shape formed by mutual condensation of primary particles and secondary particles. On the contrary, the positive electrode active material for lithium secondary batteries prepared by the above method is a small particle in a single crystal shape. In this case, lithium is evenly distributed in the above single crystal shape. In addition, the above single crystal shape exists in a state where the particles are separated individually, and the average particle size can be 1 μm to 5 μm. In addition, the above single crystal shape can be a layered structure without impurities.

[0063] The positive electrode active material for lithium secondary battery prepared by the above method is a small particle in the shape of a single crystal, wherein, when nanoparticles of hundreds of nm in size are mixed, a bimodal shape can be embodied. Therefore, more preferably, when preparing a pole plate, the compaction density can be increased to develop a high-capacity battery, and the characteristics under high temperature conditions are also improved.

[0064] Lithium secondary battery

[0065] The present invention provides a lithium secondary battery including the positive electrode active material.

[0066] The lithium secondary battery of the present invention includes the above-mentioned positive electrode active material. The “positive electrode active material” has been described above, and therefore, repeated description will be omitted.

[0067] Specifically, the present invention can provide a lithium secondary battery, the lithium secondary battery comprising: a positive electrode, comprising the positive electrode active material, a conductive material and a binder; a negative electrode, comprising the negative electrode active material; and an electrolyte. The lithium secondary battery comprises a positive electrode, a negative electrode and a separator, and the separator between the positive electrode and the negative electrode for insulating the plurality of electrodes can be a known polyolefin substrate separator or a composite separator having an organic-inorganic composite layer formed on the polyolefin substrate, but is not particularly limited.

[0068] Furthermore, the present invention can provide a medium-to-large battery module or battery pack including a plurality of the above-mentioned lithium secondary batteries electrically connected. The above-mentioned medium-to-large battery module or battery pack can be used as a power tool (Power Tool); electric vehicles including electric vehicles (EV), hybrid electric vehicles (HEV) and plug-in hybrid electric vehicles (PHEV); electric trucks; electric commercial vehicles or at least one medium-to-large equipment power supply in an energy storage system.

[0069] As described above, the method for preparing a positive electrode active material for a lithium secondary battery of the present invention eliminates the use of a transition metal precursor, performs wet nano-grinding on a solution for dissolving and dispersing each raw material (raw material in oxide form or hydroxide form), and then puts it into a planetary disperser and performs mechanical drying, so that a single crystal-shaped lithium-containing compound can be easily prepared with high efficiency. Depending on the situation, each raw material uses a raw material obtained from a lithium ion waste battery by a wet process, which can solve the environmental problems that occur when preparing a transition metal precursor, especially the water pollution problem.

[0070] The positive electrode active material for lithium secondary batteries prepared according to the present invention can stabilize the crystalline structure compared with the polycrystalline shape as lithium is evenly distributed in the single crystal shape. As a result, under high voltage charging conditions, the structural stability is excellent, thereby ensuring the high capacity characteristics of the lithium secondary battery, and the characteristics under high temperature conditions are also excellent, thereby ensuring the high temperature life, recovery and maintenance characteristics of the lithium secondary battery. In particular, compared with the polycrystalline shape, the thermal stability is excellent, thereby improving the stability of the lithium secondary battery.

[0071] That is, the lithium secondary battery using the high-performance and low-cost positive electrode active material prepared according to the present invention has excellent performance such as discharge capacity, efficiency, C-rate, and normal temperature and high temperature life characteristics.

[0072] The following preferred embodiments are provided to help understand the present invention. However, the following embodiments are provided to make the present invention easier to understand, and the content of the present invention is not limited to the following embodiments.

[0073] Example

[0074] Example 1

[0075] Li2CO3 was prepared as a lithium-containing raw material. In addition, Ni(OH)2 as a nickel-containing raw material, Co3O4 as a cobalt-containing raw material, and Mn3O4 as a manganese-containing raw material were prepared in a combination ratio (equivalent ratio) of Ni:Co:Mn=6:2:2. Each raw material was used under the condition of Li / Me=1.5 and water was used as a solvent. Figure 1a In this case, the weight ratio of each raw material to water was changed to 1:2 to 1:4. The results of the test showed that the best dissolution and dispersion effect was achieved when the weight ratio of each raw material to water was 1:3.

[0076] For dissolving and dispersing solutions, use Figure 1b After preparing nano-slurry by wet nano-grinding for 1 to 3 hours using the wet nano-grinding equipment shown in the figure, the particle size distribution ( Figure 1c ). As a result, after 2 hours of wet nano-grinding at a speed of 3000 rpm, the measured particle distribution is D50 = 0.1 to 0.5 μm (preferably, 0.1 to 0.2 μm), Dmax < 1 μm. In this case, after mechanical drying and sintering, a positive electrode active material for a lithium secondary battery with excellent performance can be prepared by uniform particle growth.

[0077] Put the nano slurry into Figure 1d After the planetary dispersive mixer shown in the figure, air or dry nitrogen is blown in under vacuum conditions and mechanical drying is performed to prepare nanoparticles. In this case, a jacket having a circulation flow path for circulating a heating fluid at about 100° C. is further provided on the outer surface of the planetary dispersive mixer.

[0078] The nanoparticles were classified by -325 mesh, calcined at 850 to 900° C. for 10 hours in an oxygen atmosphere, and then pulverized by a pulverizer to prepare a lithium-containing compound [LNCM622] (D50=1 to 5 μm) in a single crystal form.

[0079] Next, after preparing the positive electrode active material slurry with a weight ratio of single-crystal lithium-containing compound [LNCM622]: Super P conductive material: polyvinylidene fluoride binder = 96:2:2, the positive electrode plate was prepared at a plate density of 3.3g / cc, and a button cell was prepared in a dry room using a Li metal negative electrode and EC / DMC / DEC[1 / 1 / 1]+1M LiPF6 electrolyte. After that, the normal temperature life and 45°C high temperature life were evaluated at 0.1C capacity, C-rate and 1C / 1C conditions in the voltage range of 4.3-3.0V, 4.4-3.0V, and 4.5-3.0V.

[0080] Example 2

[0081] Li2CO3 was prepared as a lithium-containing raw material. In addition, a single-crystal lithium-containing compound [LNCMA613] (D50 = 1 to 5 μm) and a button cell were prepared by the same method as in Example 1, except that Ni(OH)2 as a nickel-containing raw material, Co3O4 as a cobalt-containing raw material, Mn3O4 as a manganese-containing raw material, and Al2O3 powder of less than 10 μm in size as an aluminum-containing raw material were replaced by a combination ratio (equivalent ratio) of Ni:Co:Mn:Al = 6:1:2.3:0.7. After that, the normal temperature life and 45°C high temperature life were evaluated under 0.1C capacity, C-rate and 1C / 1C conditions in the voltage range of 4.3-3.0V, 4.4-3.0V, and 4.5-3.0V.

[0082] Comparative Example 1

[0083] Using NCMA613 precursor [Ni 0.6 Co 0.1 Mn 0.23 Al 0.07 (OH)2, China Zhongwei (CNCR) company product, D50 = 10 ~ 11um] and Li2CO3 [made in China], measured at Li / Me = 1.05, after 1 hour of dry mixing using a mixer, sintered at 850 ~ 900 ° C in an air atmosphere for 10 hours. Then, after pulverizing using a roller mill and an ACM pulverizer, the pulverized powder was classified by -325 mesh (mesh), thereby preparing Ni-containing lithium compound as a polycrystalline form. 0.6 Co 0.1 Mn 0.23 Al 0.07 O2[LNCMA613](D50=10~50μm).

[0084] Next, Ni 0.6 Co 0.1 Mn 0.23 Al 0.07 After the positive electrode active material slurry was made with a weight ratio of O2[LNCMA613]:Super P conductive material:polyvinylidene fluoride binder=96:2:2, the positive electrode plate was prepared at a plate density of 3.3g / cc, and the button cell was prepared in a dry room using a Li metal negative electrode and EC / DMC / DEC[1 / 1 / 1]+1M LiPF6 electrolyte. After that, the normal temperature life and 45°C high temperature life were evaluated at 0.1C capacity, C-rate and 1C / 1C conditions in the voltage range of 4.3-3.0V, 4.4-3.0V, and 4.5-3.0V.

[0085] Figure 2a and Figure 2bIn order to compare the c-rate and 0.1C capacity in the voltage range of 4.5-3.0V of the button batteries of Example 2 and Comparative Example 1, respectively, the button battery of Example 2 excludes the use of NCMA613 precursor and is put into a wet nano grinder and a planetary disperser for mechanical drying. Compared with the button battery of Comparative Example 1, the c-rate and 0.1C capacity in the voltage range of 4.5-3.0V are excellent.

[0086] Example 3

[0087] Li2CO3 was prepared as a lithium-containing raw material. In addition, a single-crystal lithium-containing compound [LNFA] (D50 = 1-5 μm) and a button cell were prepared by the same method as in Example 1, except that Ni:Fe:Al = 8.5:0.52:0.91 was used to replace NiO as a nickel-containing raw material, Fe2O3 as an iron-containing raw material, and Al2O3 as an aluminum-containing raw material. Afterwards, the normal temperature life and 45°C high temperature life were evaluated under 0.1C capacity, C-rate and 1C / 1C conditions in the voltage range of 4.3-3.0V, 4.4-3.0V, and 4.5-3.0V.

[0088] Comparative Example 2

[0089] Referring to the contents disclosed in Journal of Power Sources.2020.Doi:10.1016 / j.jpowsour.2020.228389 ("a new cobalt-free layered cathode material for advanced Li-ion batteries"), Ni as a NFA precursor x Fe y Al z (OH)2 prepared Li as a lithium-containing compound in polycrystalline form 1.0 Ni 0.85 Fe 0.052 Al 0.091 O2 (D50 = 10 ~ 50μm).

[0090] Next, Li 1.0 Ni 0.85 Fe 0.052 Al 0.091After preparing the positive active material slurry with a weight ratio of O2[NFA]:Super P conductive material:polyvinylidene fluoride binder=96:2:2, the positive electrode plate was prepared at a plate density of 3.3g / cc, and the button cell was prepared in a dry room using a Li metal negative electrode and EC / DMC / DEC[1 / 1 / 1]+1M LiPF6 electrolyte. After that, the normal temperature life and 45°C high temperature life were evaluated at 0.1C capacity, C-rate and 1C / 1C conditions in the voltage range of 4.3-3.0V, 4.4-3.0V, and 4.5-3.0V.

[0091] Figure 3 The charts for comparing the 0.1C capacity in the voltage ranges of 4.5-3.0V and 4.3-3.0V of the button cells of Example 3 and Comparative Example 2 show that the 0.1C capacity of the button cell of Comparative Example 2 in the voltage range of 4.3-3.0V is about 160mAh / g, while the 0.1C capacity of the button cell of Example 3 in the voltage range of 4.3-3.0V is about 170mAh / g, confirming that the discharge capacity is improved. This can be the result of excluding the use of NFA precursors and mechanically drying after being put into a wet nano-grinder and a planetary disperser.

[0092] Example 4

[0093] Li2CO3 was prepared as a lithium-containing raw material. In addition, a single-crystal lithium-containing compound [5V LNMO] (D50 = 1-5 μm) and a button cell were prepared by the same method as in Example 1, except that Ni:Mn = 2.5:7.5 was used as a combination ratio (equivalent ratio) to replace Ni(OH)2 as a nickel-containing raw material and Mn3O4 as a manganese-containing raw material. After that, the normal temperature life and 45°C high temperature life were evaluated under 0.1C capacity, C-rate and 1C / 1C conditions in the voltage range of 4.9-3.0V.

[0094] Comparative Example 3

[0095] Using NMO precursor [Ni 0.25 Mn 0.75 (OH)2, China Zhongwei (CNCR) company product, D50 = 10 ~ 11um] and Li2CO3 [made in China], measured at Li / Me = 1.03, after 1 hour of dry mixing using a mixer, sintered at 800 ~ 850 ° C in an air atmosphere for 10 hours. Then, after pulverizing using a roller mill and an ACM pulverizer, the mixture was classified by -325 mesh, thereby preparing LiNi as a polycrystalline lithium-containing compound. 0.25 Mn 0.75 O4[5V LNMO](D50=10~50μm).

[0096] Next, LiNi 0.25 Mn 0.75 After preparing the positive active material slurry with a weight ratio of O4[5V LNMO]:Super P conductive material:polyvinylidene fluoride binder=96:2:2, the positive electrode plate was prepared at a plate density of 3.3g / cc, and the button cell was prepared in a dry room using a Li metal negative electrode and EC / DMC / DEC[1 / 1 / 1]+1M LiPF6 electrolyte. After that, the normal temperature life and 45°C high temperature life were evaluated at 0.1C capacity, C-rate and 1C / 1C conditions in the voltage range of 4.9-3.0V.

[0097] Figure 4a To compare the SEM photos of the lithium-containing compounds of Example 4 and Comparative Example 3, the lithium-containing compound of Example 4 is a single crystal shape with an average particle size of 1 to 5 um in which the particles are individually separated, and the lithium-containing compound of Comparative Example 3 is a polycrystalline shape formed by the condensation of primary particles and secondary particles.

[0098] and, Figure 4b 4C is a chart comparing the 0.1C capacity and room temperature life of the button cells of Example 4 and Comparative Example 3 in the voltage range of 4.9-3.0V. Compared with the button cell of Comparative Example 3, the button cell of Example 4 has the same level of discharge capacity, and the room temperature life characteristics are significantly improved. This can be the result of excluding the use of NMO precursors, and mechanically drying after being put into a wet nano-grinder and a planetary disperser, and uniformly distributing lithium in a single crystal shape.

[0099] Example 5

[0100] Li2CO3 was prepared as a lithium-containing raw material. In addition, a single-crystal lithium-containing compound [LNCM523] (D50 = 1-5 μm) and a button cell were prepared by the same method as in Example 1, except that Ni(OH)2 as a nickel-containing raw material and Mn3O4 as a manganese-containing raw material were replaced by a combination ratio (equivalent ratio) of Ni:Co:Mn = 5:2:3. Afterwards, the normal temperature life and 45°C high temperature life were evaluated under 0.1C capacity, C-rate and 1C / 1C conditions in the voltage range of 4.3-3.0V, 4.4-3.0V, and 4.5-3.0V.

[0101] Comparative Example 4

[0102] Using NCM523 precursor [Ni 0.5 Co 0.2 Mn 0.3(OH)2, China Zhongwei (CNCR) company product, D50 = 10 ~ 11um] and Li2CO3 [made in China], measured at Li / Me = 1.05, after 1 hour of dry mixing using a mixer, calcined at 900 ~ 950 ° C in an air atmosphere for 10 hours. Then, after crushing using a roller mill and an ACM crusher, it was classified by -325 mesh, thereby preparing LiNi as a polycrystalline lithium-containing compound. 0.5 Co 0.2 Mn 0.3 O2[LNCM523](D50=10~50μm).

[0103] Next, LiNi 0.5 Co 0.2 Mn 0.3 After the positive electrode active material slurry was made with a weight ratio of O2[LNCM523]:Super P conductive material:polyvinylidene fluoride (PVDF) binder = 96:2:2, the positive electrode plate was prepared at a plate density of 3.3g / cc, and the button cell was prepared in a dry room using a Li metal negative electrode and EC / DMC / DEC[1 / 1 / 1]+1M LiPF6 electrolyte. After that, the normal temperature life and 45°C high temperature life were evaluated at 0.1C capacity, C-rate and 1C / 1C conditions in the voltage range of 4.3-3.0V, 4.4-3.0V, and 4.5-3.0V.

[0104] Figure 5a This is a graph showing an XRD pattern of the lithium-containing compound of Example 5. The lithium-containing compound of Example 5 showed a single-phase peak of a layered structure, and thus it was confirmed that a layered structure was formed without generating impurities.

[0105] and, Figure 5b To compare the SEM photographs of the lithium-containing compounds of Example 5 and Comparative Example 4, the lithium-containing compound of Example 5 is a single crystal shape with an average particle size of 1 to 5 μm in which the particles are individually separated, and the lithium-containing compound of Comparative Example 4 is a polycrystalline shape in which primary particles and secondary particles are condensed with each other.

[0106] and, Figure 5c The chart comparing the 0.1C capacity in the voltage range of 4.3-3.0V of the button cells of Example 5 and Comparative Example 3 shows that the yield point capacity and efficiency of the button cell of Example 5 are improved compared with the button cell of Comparative Example 3. This is because the use of the NCM523 precursor is eliminated, and the wet nano-grinding and mechanical drying after the planetary disperser are performed, so that lithium is evenly distributed in the single crystal shape formed into a layered structure, and no impurities are generated.

[0107] Example 6

[0108] LiOH was prepared as a lithium-containing raw material. In addition, Ni(OH)2 was used as a nickel-containing raw material and Mn3O4 was used as a manganese-containing raw material, both of which were obtained from lithium-ion waste batteries by a wet process. Specifically, the positive electrode plate of the lithium-ion waste battery was dissolved with acid, and then precipitated by positive ion metal titration to obtain the hydroxide form in the intermediate stage, and the oxide form in the final stage was obtained through a heat treatment and sintering process. That is, in addition to replacing the Ni:Mn=8:2 combination ratio (equivalent ratio), and also adding A=Al2O3[2000~3000ppm] and B=TiO2[500~1000ppm] as doped metal oxides, a single crystal lithium-containing compound [Co-free LNM8020_used recycled metal] (D50=1~5μm) and a button battery were prepared by the same method as in Example 1. Afterwards, the normal temperature life and 45°C high temperature life were evaluated in the voltage range of 4.3-3.0V, 4.4-3.0V, and 4.5-3.0V with 0.1C capacity, C-rate, and 1C / 1C conditions.

[0109] Figure 6a and Figure 6b The graphs show the 0.1C capacity and high temperature life of the button battery of Example 6 in the voltage ranges of 4.3-3.0V and 4.4-3.0V, respectively. The button battery of Example 6 has excellent discharge capacity and excellent high temperature life characteristics.

[0110] Example 7

[0111] First, Fe2O3 as an iron-containing raw material and (NH4)3HPO4 as a PO4-containing raw material were prepared in a combination ratio of Fe:PO4=1:1 (equivalent ratio) and dry-mixed, and then pre-sintered at 160-180°C for 15-18 hours in a nitrogen atmosphere to prepare single-phase single crystal FePO4. In addition, Li2CO3 was prepared as a lithium-containing raw material. Each raw material was used as a solvent under the condition of Li / Me=1.05, and water was used as a solvent. Figure 1a In this case, the weight ratio of each raw material to water was changed to 1:2 to 1:4. The results of the test showed that the best dissolution and dispersion effect was achieved when the weight ratio of each raw material to water was 1:3.

[0112] The dissolved and dispersed solution was subjected to wet nano-milling at a speed of 3000 rpm for 2 hours using the wet nano-milling equipment used in Example 1 to prepare a nano-slurry.

[0113] After the nano slurry was put into the planetary disperser used in Example 1, dry air was blown in under vacuum conditions and mechanical drying was performed to prepare nano particles. In this case, a jacket having a circulation flow path for circulating a heating fluid at about 100° C. was also provided on the outer surface of the planetary disperser.

[0114] The nanoparticles were calcined at 730 to 770° C. for 10 hours in a nitrogen atmosphere and then pulverized using a pulverizer to prepare a single-crystal lithium-containing compound [LFP] (D50=1 to 5 μm).

[0115] Next, a single-crystal lithium-containing compound [LFP]: Super P conductive material: polyvinylidene fluoride binder = 95:2.5:2.5 weight ratio was used to make a positive electrode active material slurry, and a positive electrode plate was prepared at a plate density of 2.0g / cc. A button cell was prepared in a dry room using a Li metal negative electrode and EC / DMC / DEC[1 / 1 / 1]+1M LiPF6 electrolyte. After that, the normal temperature life and 45°C high temperature life were evaluated in the voltage range of 3.7-2.0V with 0.1C capacity, C-rate and 1C / 1C conditions.

[0116] Comparative Example 5

[0117] Using the FP precursor (FePO4, a product of China Zhongwei (CNCR) Company, a product with a size of several hundred nanometers (D50 = 100-300nm)) prepared by the coprecipitation method and Li2CO3 [made in China], after measuring at Li / Me = 1.05, 3-5wt% of glucose was added to the total weight, and then dry mixed for 1 hour using a mixer, and then calcined for 10 hours at 600-700°C under a nitrogen atmosphere. Then, after pulverizing using a roller mill and an ACM pulverizer, the mixture was classified using -325mesh, thereby preparing LiFePO4[LFP] (D50 = 100-500nm) as a lithium-containing compound.

[0118] Next, as a lithium-containing compound, LiFePO4[LFP]:Super P conductive material: polyvinylidene fluoride binder = 95:2.5:2.5 weight ratio was used to prepare the positive electrode active material slurry, and the positive electrode plate was prepared at a plate density of 2.0g / cc. The button battery was prepared in a dry room using a Li metal negative electrode and EC / DMC / DEC[1 / 1 / 1]+1M LiPF6 electrolyte. After that, the normal temperature life and 45°C high temperature life were evaluated at 0.1C capacity, C-rate and 1C / 1C conditions in the voltage range of 3.7-2.0V.

[0119] Figure 7aThe SEM photograph of the lithium-containing compound of Example 7 for comparison confirmed that the lithium-containing compound of Example 7 was in a single crystal shape with an average particle size of 1 to 5 μm in which individual particles were separated.

[0120] and, Figure 7b The chart comparing the XRD patterns of the lithium-containing compound of Example 7 at each sintering temperature shows that when the sintering temperature is 730-770°C, the lithium-containing compound of Example 7 exhibits a single-phase peak of a layered structure and forms a layered structure without generating impurities.

[0121] Figure 7c to Figure 7e Part of the diagram is a comparison of the 0.1C capacity, high temperature life and C-rate of the button cells of Example 5 and Comparative Example 5 in the voltage range of 3.7-2.0V. Compared with the button cell of Comparative Example 5, the discharge capacity and efficiency of the button cell of Example 7 are improved, and the high temperature life characteristics and C-rate are excellent. This is because the use of the FP precursor prepared by the coprecipitation method is eliminated, and mechanical drying is performed after being put into a wet nano-grinder and a planetary disperser, so that lithium is evenly distributed in the single crystal shape formed into a layered structure, and no impurities are generated.

[0122] Example 7 - Example 1

[0123] The single crystal lithium-containing compound [LFP] (D50 = 1-5 μm) prepared in Example 7 and the LiFePO4 [LFP] (D50 = 100-500 nm) prepared in Comparative Example 5 were mixed in a weight ratio of 7:3 to prepare a bimodal lithium-containing compound and a button cell. 2 The plate density and substrate energy density were measured by applying a pressure of , and are presented in Table 1.

[0124] Table 1

[0125]

[0126] As shown in Table 1, it was confirmed that the electrode density of the button cell of Example 7-Example 1 increased by about 21% and the energy density increased by about 25% compared with the button cell of Comparative Example 5. This is the best improvement in the compaction density when preparing the electrode plate.

[0127] Example 8

[0128] LiOH was prepared as a lithium-containing raw material. In addition, a single-crystal lithium-containing compound [LNMCM83] (D50 = 1-5 μm) and a button cell were prepared by the same method as in Example 1, except that Ni(OH)2 as a nickel-containing raw material, Co3O4 as a cobalt-containing raw material, and Mn3O4 as a manganese-containing raw material were replaced by a combination ratio (equivalent ratio) of Ni:Co:Mn = 8.3:1.2:0.5, and MoO6 [3000 ppm] was added as a doped metal oxide. Afterwards, the normal temperature life and 45°C high temperature life were evaluated under 0.1C capacity, C-rate, and 1C / 1C conditions in the voltage range of 4.3-3.0V, 4.4-3.0V, and 4.5-3.0V.

[0129] Figure 8 As a graph confirming the 0.1C capacity in the voltage range of 4.3-3.0 V of the button cell of Example 5, it is confirmed that the discharge capacity and efficiency of the button cell of Example 5 are quite excellent. As the doped metal oxide, MoO6 is particularly preferred.

[0130] The above description of the present invention is for illustration only, and a person skilled in the art can easily transform the present invention into other specific forms without changing the technical concept or essential features of the present invention. Therefore, the above described embodiments are illustrative in all aspects and are not restrictive.

Claims

1. A method for preparing a positive electrode active material for a lithium secondary battery, characterized in that: include: Step (a), respectively preparing a first raw material containing a lithium-containing raw material and a second raw material containing at least one selected from the group consisting of a nickel-containing raw material, a cobalt-containing raw material, a manganese-containing raw material, an iron-containing raw material and an aluminum-containing raw material; Step (b), preparing a nano-slurry by wet nano-grinding the solution in which the first raw material and the second raw material are dissolved and dispersed; Step (c), adding the nano-slurry into a planetary disperser and then mechanically drying to prepare nano-particles; as well as Step (d) sintering the mechanically dried nanoparticles to prepare a lithium-containing compound in a single crystal form.

2. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: In the above step (a), the second raw material is in the form of an oxide or a hydroxide.

3. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: In the above step (a), i) when the second raw material contains both a nickel-containing raw material and a manganese-containing raw material, it further contains at least one doping metal oxide selected from the group consisting of aluminum oxide, titanium dioxide, zirconium dioxide, molybdenum oxide and tantalum pentoxide, ii) When the second raw material contains an iron-containing raw material, it also contains a PO4-containing raw material.

4. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 3, characterized in that: The method further comprises step ii), wherein after dry mixing the second raw material containing the above-mentioned iron-containing raw material and the PO4-containing raw material, pre-calcination is performed at a temperature of 150° C. to 200° C. for 5 to 20 hours.

5. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: In the above step (b), the volume ratio of the above raw materials to the solvent in the solution is 1:1 to 1:

5.

6. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: In the above step (b), the wet nano-milling is performed at a speed of 1000 rpm to 5000 rpm for 1 hour to 5 hours.

7. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: In the above step (b), in the particle distribution of the nano-slurry, 0.1 μm≤D50≤0.5 μm, Dmax<1 μm.

8. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: In the above step (c), a jacket having a circulation flow path for circulating a heating fluid is further provided on the outer surface of the planetary disperser, and the heating fluid is maintained at a temperature of 50°C to 200°C.

9. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: In the above step (c), the mechanical drying is performed under vacuum conditions.

10. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: In the above step (d), the firing is performed at a temperature of 600° C. to 1000° C. for 5 to 20 hours.

11. The method for preparing a positive electrode active material for a lithium secondary battery according to claim 1, characterized in that: After the above step (d), the method further includes forming a surface treatment layer on the above single crystal lithium-containing compound, wherein the surface treatment layer contains Al(OH) 3 , a boron-containing compound and a silicon-containing compound.

12. A positive electrode active material for a lithium secondary battery, characterized in that: Prepared by the method according to any one of claims 1 to 11.

13. A lithium secondary battery, characterized in that: Contains the positive electrode active material according to claim 12.